Living Rights Festival Art Exhibition: Bertha House, 25 Oct 24 - Living Rights Festival; Sitas, Ari (New Agenda: SA Journal of Social and Economic Policy, 2025)
What is the Living Rights Festival about? In response to escalating global conflicts and deepening humanitarian crises, the Living Rights Festival seeks to ignite and inform public discussion on these urgent issues and mobilise a robust civil society response. Born from a profound commitment to peaceful coexistence, social justice, and human rights, this Cape Town-based, community-led initiative addresses the growing violence and injustice that threaten our collective future. The festival is not merely an event but a movement—a call to action for individuals and communities worldwide to stand in solidarity with those whose rights are under siege. By focusing on our shared humanity, the Living Rights Festival offers a platform to confront injustice, advocate for essential freedoms, and inspire a new vision of global peace and dignity. Set against the backdrop of Cape Town, a city renowned for its resilience and activism, the festival will address some of the most pressing challenges of our time, including genocide, militarisation, racism, climate change, social accountability and the looming threat of nuclear conflict. Launching in October, a month dedicated to global peace and security, the festival aims to build understanding, foster solidarity, and inspire proactive engagement through a dynamic programme of educational and cultural events. The festival’s diverse programming includes thought-provoking forums, powerful performances, and interactive workshops, all designed to deepen understanding and strengthen community bonds. These key events will explore international law’s role in addressing genocide accusations, the complexities of North-South relationships, and the destructive influence of the global arms industry, alongside cultural showcases of resilience and creativity. The Living Rights Festival represents a bold step towards a more just and peaceful world, advocating for the protection of human rights and the prevention of future atrocities. The community organisations leading this initiative are committed to making the festival an annual event, ensuring sustained advocacy and action for years to come.